SARIDIN IN THE STRUGGLE BETWEEN ISLAM AND TRADITION: The Relevance of Islamism of Saridin for Character Education of Coastal Communities - Nur Said (Asia-Pacific Journal on Religion and Society, 2022)
This article is a research on the "people religion" that the Sedulur Sikep community of Pati, Central Java, considers as a belief pattern and value system that in fact constitute the unique identity of Islam. It starts with the existence of Sariddin, who later changed his identity to Sheikh Jangkung, and his struggle between Islam and local culture as an effort to actualize local cultural values in character-building education. The affirmation of Islamic teachings developed by Saridin with popular local cultural symbols and systems makes character education easy to digest and live with cultural awareness and cultural intelligence